The Economics of Human Cloning - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2000)
In this paper, we analyze the extent to which market forces create an incentive for cloning human beings. We show that a market for cloning arises if a large enough fraction of the clone?s income can be appropriated by its model. Only people with the highest ability are cloned, while people at the bottom of the distribution of income specialize in surrogacy. In the short run, cloning reduces inequality. In the long run, it creates a perfectly egalitarian society where all workers have a top ability if fertility is uncorrelated with ability and if the distribution of ability among sexually produced children is the same as among their parents. In such a society, cloning has disappeared. If the distribution of genes, rather than abilities, is preserved by sexual reproduction, then cloning eliminates ability-reducing genes but does not necessarily eliminate inequality; nor does it disappear in the long run. Finally, if fertility is negatively correlated with ability, in the long run a reproductive caste of bottom ability people coexist with a cloned, worker caste of top ability agents, while intermediate ability types have disappeared.
Keywords: J13; O15; J31; J24; J12; 330; Human capital; income distribution; human cloning; overlapping generations; intergenerational mobility; Gentechnik; Kosten-Nutzen-Analyse; Humankapital; Einkommensverteilung; Overlapping Generations; Theorie